RELATED IMPACT FROM SERVICE QUALITY AND PRODUCT QUALITY TOWARDS CUSTOMER SATISFACTION AS WELL AS ITS IMPLICATIONS TO CUSTOMER LOYALTY AT PT. CIANJUR ARTHA MAKMUR - Adi Dharmawan, Dwian; Arifin Sitio (Dinasti International Journal of Management Science, 2020)
This research aims to find out those influence from Service Quality, and Product Quality towards Customer Satisfaction and its Implications to Customer Loyalty at PT. Cianjur Artha Makmur. This type of research were catagorized as descriptive analytics research. While population were customers from PT Cianjur Artha Makmur (CAM) totalling of 543 customers according to 2018 company's internal data. These research used Slovin formula to estimates these sample size needed and it obtained 100 respondents. The analysis technique used path analysis through SPSS version 23. The results from this research was indicate that (1) Service Quality has huge impact to Customer Satisfaction (2) Product Quality has significant influence over Customer Satisfaction (3) Service Quality has marked effect to Customer Loyalty (4) Product Quality has undefinable affects towards Customer Loyalty and (5) Customer Satisfaction has huge impact on Customer Loyalty.